The identification of problems in action research (Journal of Parents and Teachers, 2014)
Teachers are asked to be questioned, asked questions about their practices in the classroom and seek to solve them through alternative solutions. In this issue of Padres y Maestros, a set of useful tools and procedures is offered to identify research problems and to solve them effectively.
Keywords: questions; reflection; investigation; problems.